Differential functional patterns of memory CD4+ and CD8+ T-cells from volunteers immunized with Ty21a typhoid vaccine observed using a recombinant Escherichia coli system expressing S. Typhi proteins. Issue 2 (10th January 2020) - Salerno-Gonçalves, Rosângela; Tettelin, Hervé; Luo, David; Guo, Qin; Ardito, Matthew T.; Martin, William D.; De Groot, Anne S.; Sztein, Marcelo B.
Abstract: It is widely accepted that CD4 + and CD8 + T-cells play a significant role in protection against Salmonella enterica serovar Typhi ( S. Typhi), the causative agent of the typhoid fever. However, the antigen specificity of these T-cells remains largely unknown. Previously, we demonstrated the feasibility of using a recombinant Escherichia coli ( E. coli ) expression system to uncover the antigen specificity of CD4 + and CD8 + T cells. Here, we expanded these studies to include the evaluation of 12 additional S . Typhi proteins: 4 outer membrane proteins (OmpH, OmpL, OmpR, OmpX), 3 Vi-polysaccharide biosynthesis proteins (TviA, TviB, TviE), 3 cold shock proteins (CspA, CspB, CspC), and 2 conserved hypothetical proteins (Chp 1 and Chp2), all selected based on the bioinformatic analyses of the content of putative T-cell epitopes. CD4 + and CD8 + T cells from 15 adult volunteers, obtained before and 42 days after immunization with oral live attenuated Ty21a vaccine, were assessed for their functionality ( i.e ., production of cytokines and cytotoxic expression markers in response to stimulation with selected antigens) as measured by flow cytometry. Although volunteers differed on their T-cell antigen specificity, we observed T-cell immune responses against all S . Typhi proteins evaluated. These responses included 9 proteins, OmpH, OmpR, TviA, TviE, CspA, CspB, CspC, Chp 1 and Chp 2, which have not been previously reported to elicit T-cell responses. Interestingly, we also observed that, regardless of the protein, the functional patterns of the memory T-cells were different between CD4 + and CD8 + T cells. In sum, these studies demonstrated the feasibility of using bioinformatic analysis and the E. coli expressing system described here to uncover novel immunogenic T-cell proteins that could serve as potential targets for the production of protein-based vaccines .